"What shall I do when I grow up?" Adolescents with cancer on the Youth Project in Milan play with their imagination and photography. Issue 3 (June 2019) - Gaggiotti, Paola; Veneroni, Laura; Signoroni, Stefano; Silva, Matteo; Chisari, Marco; Casanova, Michela; Chiaravalli, Stefano; Sironi, Giovanna; Clerici, Carlo Alfredo; Proserpio, Tullio; Massimino, Maura; Ferrari, Andrea
Introduction: Adolescents diagnosed with cancer have to temporarily stop pursuing several vital needs and making plans for the future. The Youth Project in Milan, Italy, focuses on such issues in young cancer patients' personal lives. Uncertainty about the future had already emerged in several artistic projects designed to help these patients voice their emotions. Methods: We describe a project revolving around the question "What shall I do when I grow up?" Twenty-seven 15- to 26-year-old patients wrote a brief account of what they hoped to do as adults. Using theatrical costumes, they then dressed up in their chosen role for a photo shoot with a well-known professional photographer. The results were published in one of Italy's main national dailies. Results: Participants reacted differently: some lightheartedly, others more seriously. They often expressed the wish to help others, desiring to return the support and protection they had received as patients. Another common theme concerned their need for normality. Conclusions: By writing about their dreams, these patients gave their doctors a glimpse of their inner world. The project proved an important complement to more conventional forms of psychosocial support and interaction with young patients.